1999
DOI: 10.1006/appe.1999.0267
|View full text |Cite
|
Sign up to set email alerts
|

Consumers» Cognitions With Regard to Genetically Modified Foods. Results of a Qualitative Study in Four Countries

Abstract: The objective of this research was to gain insight into consumers>> attitudes towards genetic modification in food production. With means-end chain theory as the theoretical basis, laddering interviews were conducted with 400 consumers in Denmark, Germany, the United Kingdom and Italy. Perceived risks and benefits of genetic modification in foods were investigated using beer and yoghurt as examples. German and Danish responses revealed more complex cognitive structures than did the results from the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
169
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 13 publications
(9 reference statements)
12
169
1
5
Order By: Relevance
“…The Worldwide studies showed that consumers' concerns about GM foods are increasing, and acceptance of GM foods differs among countries (Gaskell et al, 2004;Bredahl, 1999;Curtis et al, 2004).The consumers acceptance of the GM foods plays an important role in the commercial expansion of the genetically modified food crops. The consumers' willingness to pay for GM foods is estimated by using censored least absolute deviation (CLAD) model and the result is presented in Table 4.…”
Section: Consumers' Willingness To Pay For Gm Foodsmentioning
confidence: 99%
“…The Worldwide studies showed that consumers' concerns about GM foods are increasing, and acceptance of GM foods differs among countries (Gaskell et al, 2004;Bredahl, 1999;Curtis et al, 2004).The consumers acceptance of the GM foods plays an important role in the commercial expansion of the genetically modified food crops. The consumers' willingness to pay for GM foods is estimated by using censored least absolute deviation (CLAD) model and the result is presented in Table 4.…”
Section: Consumers' Willingness To Pay For Gm Foodsmentioning
confidence: 99%
“…Some studies reported the importance . Some studies reported the importance Some studies reported the importance ome studies reported the importance studies reported the importance reported the importance of the consumers� attitudes, perceptions, and values the consumers� attitudes, perceptions, and values consumers� attitudes, perceptions, and values � attitudes, perceptions, and values attitudes, perceptions, and values associated with g� food and examined their effect and examined their effect examined their effect examined their effect their effect on consumers� behavioral intentions to buy g� food s� behavioral intentions to buy g� food behavioral intentions to buy g� food (Sparks et al 1995;Ku�nesof and ritson 1996;Bredahl 1999Bredahl , 2001grunert et al 2001;cook et al 2002). Attitude, defined as the disposition to evaluate an attitude ob�ect with some degree of favor or disfavor with some degree of favor or disfavor some degree of favor or disfavor (Eagly and chaiken 199�), is generally found to be and chaiken 199�), is generally found to be chaiken 199�), is generally found to be the strongest predictor of the behavioral intention for the behavioral intention for behavioral intention for g� food (honkanen and Verplanken 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This approach has frequently been applied to understand perceptions about, and why, consumers choose specific food products including beverages, different methods of farming (local and organic foods, and genetically modified products) and different kinds of foods (pork and vegetables) (Gutman 1984;Gengler et al 1999;Naspetti and Zanoli 2009;Hall and Lockshin 2000;Bredahl 1999;Grunert et al 2001;Makatouni 2002;Urala and Lähteenmäki 2003;Fotopoulos et al 2003;Baker et al 2004;Roininen et al 2006;Lind 2007;Krystallis et al 2008;Barrena and Sanchez 2010;Kirchhoff et al 2011;Arsil et al 2014b). MECs have also been identified as a useful method to reveal the drivers of consumers' food choices in the United States, many European countries including the United Kingdom, Denmark, Sweden, Belgium, Finland, Greece, Spain, and in Australia (Gutman 1984;Gengler et al 1995;Bech-Larsen et al 1996;Fotopoulos et al 2003;Padel and Foster 2005;Bonne and Verbeke 2006;Roininen et al 2006;Grantham 2007;Lind 2007;Krystallis et al 2008;Barrena and Sanchez 2010;Kirchhoff et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MECs have also been identified as a useful method to reveal the drivers of consumers' food choices in the United States, many European countries including the United Kingdom, Denmark, Sweden, Belgium, Finland, Greece, Spain, and in Australia (Gutman 1984;Gengler et al 1995;Bech-Larsen et al 1996;Fotopoulos et al 2003;Padel and Foster 2005;Bonne and Verbeke 2006;Roininen et al 2006;Grantham 2007;Lind 2007;Krystallis et al 2008;Barrena and Sanchez 2010;Kirchhoff et al 2011). This method is also used to compare the motivation for food choices between groups of consumers in different countries, and throughout many European countries (Grunert 1997;Bredahl 1999;Valette-Florence et al 2000;Grunert et al 2001;Baker et al 2004;Naspetti and Zanoli 2009). …”
Section: Introductionmentioning
confidence: 99%